Tinjauan Kritis Atas Pelaporan Keuangan Hotel Berbasis Syariah - Maulidatul Hasanah; Agus Sugiono; Ach. Baihaki; Aminatus Zakhra (Jurnal Simki Economic, 2024)
The purpose of this study is to review how the financial reporting process is carried out by the Cahaya Berlian Syariah Hotel. This study uses qualitative research by collecting data in the form of observations, interviews and documentation. The results of this study indicate that 1) The Cahaya Berlian Syariah Hotel uses an ijarah contract in accordance with PSAK 107, however the transactions carried out are not in accordance with the principles of sharia hotel governance because they use conventional banks so they have the potential to generate usury or non halal fund, 2) Buying and selling transaction in restaurants are in accordance with PSAK 102, however when canceling orders hotels do not calculate how much cost have been incurred in the order making process which can trigger losses for hotels and restaurants, 3) Financial reporting is not in accordance with PSAK 101, because the reporting is incomplete,. The zakat issued does not account or 2,5% of income, and the hotel does not separate non-halal funds rom conventional bank account so that the benevolent fund issued come from hotel and restaurant income.